The impact of an educational program on emergency nurses’ preparedness to care for domestic violence women victims - Tahani Khalil (22928182) (2025)
Background Domestic Violence (DV) is a worldwide problem that negatively impacts women’s health, family, and community. For that, improving emergency nurses’ competencies and preparedness regarding the care of Domestic Violence (DV) victims is crucial in nursing education. The purpose of the study was to investigate the effect of an educational program on the emergency nurses’ preparedness, perceived preparation and knowledge, actual knowledge, attitude, and practice regarding caring for DV women victims. Methods A quasi-experimental pretest-posttest one-group design was used, and the data were collected from 43 emergency nurses working in two private hospitals in Amman. The participants filled out the DV Preparedness Questionnaire (DVPQ) as a pre-test, then enrolled in a one-day educational program regarding the DV nurse’s preparedness program, and finally, again, participants filled out the DVPQ as a post-test. Results A total number of 43 nurses from two private hospitals were invited to participate in this study. All the invited nurses attended the educational program. Therefore, the response rate was 100%, and there were no attrition or withdrawal cases during the study. The results of this study showed that emergency nurses’ mean scores of DVPQ subscales regarding care of DV women victims improved after attending an educational program about DV preparedness. A significant difference in the score pre-test and post-test for emergency nurses’ DVPQ subscales was reported; this result revealed that when an educational program applies, it effectively improves emergency nurses’ care of DV victims. Conclusion There was a significant improvement in nurses’ perceived preparation and knowledge, actual knowledge, and attitude regarding caring for DV Women Victims. Other Information Published in: International Emergency Nursing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ienj.2025.101715